Risk of bacterial meningitis in young children with a first seizure in the context of fever: a systematic review and meta-analysis. - Abolfazl Najaf-Zadeh; François Dubos; Valérie Hue; Isabelle Pruvost; Ania Bennour; Alain Martinot (PLoS ONE)
Background Of major concern in any febrile child presenting with a seizure is the possibility of bacterial meningitis (BM). We did a systematic review to estimate the risk of BM among various subgroups of young children with a first seizure in the context of fever, and to assess the utility of routine lumbar puncture (LP) in children with an apparent first FS. Methods/principal findings MEDLINE, INIST, and the COCHRANE Library databases were searched from inception to December 2011 for published studies, supplemented by manual searches of bibliographies of potentially relevant articles and review articles. Studies reporting the prevalence of BM in young children presenting to emergency care with a first: i) "seizure and fever", ii) apparent simple FS, and iii) apparent complex FS were included. Fourteen studies met the inclusion criteria. In children with a first "seizure and fever", the pooled prevalence of BM was 2.6% (95% CI 0.9-5.1); the diagnosis of BM might be suspected from clinical examination in 95% of children >6 months. In children with an apparent simple FS, the average prevalence of BM was 0.2% (range 0 to 1%). The pooled prevalence of BM among children with an apparent complex FS was 0.6% (95% CI 0.2-1.4). The utility of routine LP for diagnosis of CNS infections requiring immediate treatment in children with an apparent first FS was low: the number of patients needed to test to identify one case of such infections was 1109 in children with an apparent first simple FS, and 180 in those with an apparent first complex FS. Conclusion The values provided from this study provide a basis for an evidence-based approach to the management of different subgroups of children presenting to emergency care with a first seizure in the context of fever.